Microwave energy attenuators on the basis of aluminum nitride with high level of microwave energy absorption - Chasnyk, V. I. (Technology and design in electronic equipment, 2014)
Results of experimental studies of aluminium nitride based composites with addition of silicon carbide and molybdenum having high microwave absorption are presented. The interconnection between high level of absorption and volume electrical resistance was observed: maximum absorption of 6.5±1,0 dB/mm corresponds to the electrical resistance of (4–5)·105 Ohm·m. Level of absorption of 3.5±0,5 dB/mm is revealed for the dielectric material with electrical conductivity of 1012 Ohm·m. The patterns detected during the study allow to predict the minimum and maximum levels of absorption of microwave energy in the two-phase composites based on aluminium nitride with molybdenum or silicon carbide, based on the measured volume of electrical resistance.